ANALYSIS OF SOCIAL MEDIA CONTENT IN DIGITAL MARKETING STRATEGIES ON PRODUCT MARKETING - Yuriza Rahayu Irawan; Muhammad Yusuf (Antis Publisher, 2024)
Technological advancements are reshaping human labor, particularly in the realm of marketing, where digital marketing has emerged as a powerful tool through social media platforms. General Background: The evolution of technology has enabled the creation of dynamic and engaging content that enhances marketing strategies. Specific Background: This research aims to analyze the types of content utilized as digital marketing media across social media channels. Knowledge Gap: Despite the recognized importance of content in digital marketing, there is limited comprehensive analysis of its impact on brand awareness and customer engagement. Aims: The study employs literature review and qualitative analysis to evaluate how social media content influences consumer perceptions and behaviors. Results: Findings indicate that well-crafted social media content significantly boosts brand awareness, fosters customer engagement, and enhances brand reputation. Additionally, diverse content formats contribute to stronger emotional connections with users, driving deeper engagement. Novelty: This research adds to the understanding of effective digital marketing strategies by highlighting the role of content diversity in engaging social media audiences. Implications: The insights derived from this study offer valuable guidance for marketers seeking to optimize their digital marketing efforts, emphasizing the importance of creating engaging and emotionally resonant content to strengthen brand-customer relationships.